Vpliv telovadnih vaj po metodi pilates na stabilizatorje trupa - Plaskan, Katja (Šport (Ljubljana), 2019)
The aim of this study was to determine whether the training program, consisting of pilates exercises, influences the strength of the core and how much the strength of these muscles improves after the 8-week training program. The study included 31 people (12 men and 19 women) who did pilates trainings 1-2 times per week at different locations in Slovenia. McGill's Torso Muscular Endurance Test Battery was used to test people involved in the study before and after 8-week training program. The data were processed in the SPSS program where we checked the difference between groups and compared the results of the tests before and after 8-week training program. We found that the strength of the core after 8-week pilates exercise program statistically significantly increased. We can conclude that Pilates exercises are an appropriate tools of developing the strength of the core stabilizers and consequently reducing the problems caused by lower strength of the core stabilizers.
Keywords: core muscless; exercises; McGillov test; McGill's test battery; pilates; Pilates method; sport; stabilizatorji trupa; šport; telovadne vaje; testna baterija